Hubungan Antara Penggunaan Sarana dan Prasarana Konseling dengan Keefektifan Layanan Konseling Individu - lutfianah, leli; nusantoro, eko (Universitas Negeri Semarang, 2017)
The purpose of this research is to understand there is whether a relationship between used of counseling facilities and infrastructure with effectiveness of individual counseling services in junior high schools 21 Semarang. The research is ex-post facto. The population is students who ever implement of individual counseling services in junior high schools 21 Semarang. The data collection technique uses a psychological scale. The data analysis technique uses the percentage of descriptive analysis and analysis of product moment correlation. The result indicates that used of counseling facilities and infrastructure in good criterion, effectiveness of individual counseling services in effective, and there is a positive and significant relationship between used of counseling facilities and infrastructure with effectiveness of individual counseling.